2014
DOI: 10.11648/j.sr.20140206.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Accessibility and Utilization of Electronic Information Resources on Productivity of Academic Staff in Selected Nigerian Universities

Abstract: Abstract:The aim of the paper was to investigate the effect of accessibility and utilization of electronic resources on productivity of academic staff in Nigerian universities. A survey method was used in the study, with a questionnaire as the instrument for data collection. Responses from 324 academic staff out of 586 that were surveyed were used for data analysis. Correlation analysis showed that, there was a positive correlation between accessibility and utilization of electronic resources on productivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…The resources are renowned for their depth; timeliness; currency; speed and ease with which they can be accessed; powerful searching capabilities; roundthe-clock remote accessibility; facilities for downloading, printing and copying information; a wide range of abstracts and full-text documents from globally renowned academic databases; ability to share downloads with members of research groups; ability to provide multiple access to many researchers at the same time; possibility of inclusion of audio and video content; ability to be adapted to technologies for the visually impaired; advanced functional capabilities such as hyperlinks to other relevant articles; and manipulability like the ability to link, annotate, visualise and integrate tables (Bar-llan, Peritz & Wolman 2003;Dilek-Kayaoglu 2008;Min & Yang 2010;Monopoli et al 2002;Voorbij & Ongering 2006;Zainab, Huzaimah & Ang 2006). Electronic journals have matured to be considered prerequisites for an efficient and productive academic system (Ani 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The resources are renowned for their depth; timeliness; currency; speed and ease with which they can be accessed; powerful searching capabilities; roundthe-clock remote accessibility; facilities for downloading, printing and copying information; a wide range of abstracts and full-text documents from globally renowned academic databases; ability to share downloads with members of research groups; ability to provide multiple access to many researchers at the same time; possibility of inclusion of audio and video content; ability to be adapted to technologies for the visually impaired; advanced functional capabilities such as hyperlinks to other relevant articles; and manipulability like the ability to link, annotate, visualise and integrate tables (Bar-llan, Peritz & Wolman 2003;Dilek-Kayaoglu 2008;Min & Yang 2010;Monopoli et al 2002;Voorbij & Ongering 2006;Zainab, Huzaimah & Ang 2006). Electronic journals have matured to be considered prerequisites for an efficient and productive academic system (Ani 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, Aliyu, Younus and Tasmin (2012) revealed that accessibility influenced adoption and utilisation of electronic banking among the staff of Bayero University, Kano. Ani, Ngulube and Onyancha (2014) also found a positive correlation between accessibility and utilisation of EIR among academic staff especially at the University of Ibadan. On the contrary, Park (2009) investigation found that system accessibility has no effect on use of e-learning among Konkuk University students in Seoul, Korea.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Reporting on the use of Research4Life databases, ITOCA (2008) identified accessibility as a major problem affecting Research4Life databases utilisation in developing countries. This assertion was supported by Ani, Ngulube and Onyancha (2014) that the level of accessibility and utilisation of electronic resources in Nigeria is low when compared with that of developed countries due to lack of ICT infrastructural facilities. However, this trend is gradually changing as ITOCA (2013) finding showed that accessibility to Research4Life and TEEAL has improved.…”
Section: Literature Reviewmentioning
confidence: 97%
“…All researchers agree that information literacy creates the foundation for lifelong learning through the process of students assuming control for their own learning (American Association of College and Research Libraries [ACRL], 2000; Lakos & Phipps, 2004;Phillips & Kearley, 2003). Ani, Ngulube, and Onyancha (2014) and Sivathassan and Velnampy (2013) had reported both faculty and students' use of e-resources to access information available worldwide for teaching, learning, and research. Ani, Ngulube, and Onyancha (2014) drew a result between electronic and information resources (EIRs) accessibility and utilization on the productivity of academic staff in surveyed universities and reported a positive correlation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ani, Ngulube, and Onyancha (2014) and Sivathassan and Velnampy (2013) had reported both faculty and students' use of e-resources to access information available worldwide for teaching, learning, and research. Ani, Ngulube, and Onyancha (2014) drew a result between electronic and information resources (EIRs) accessibility and utilization on the productivity of academic staff in surveyed universities and reported a positive correlation. It explained that increase in access and use of e-resources will lead to increased productivity of academic staff.…”
Section: Literature Reviewmentioning
confidence: 99%